Kajian Penerapan Identitas Perusahaan pada Fasad Bangunan : (Studi Kasus: Kantor WU Tower Nabati di Jl. Dr. Djunjunan Bandung & Kantor HO Soetta Nabati di Jl. Soekarno Hatta Bandung) - Fajar Taufik Hidayat; Hartanto Budiyuwono (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
In an increasingly competitive business environment, the physical representation of a company such as its office building plays a crucial role in establishing corporate identity and image. This study examines how corporate identity elements are applied to the facade of WU Tower Nabati and HO Soetta Nabati office buildings in Bandung. Using a descriptive qualitative approach and referring to Francis D.K. Ching’s theory on facade elements, six corporate identity criteria corporate image, logo, brand, brand awareness, brand image, and corporate color are analyzed through visual observation. The results show that both buildings do not fully reflect the company’s identity through their facades. WU Tower performs better in presenting a professional image and strong brand perception, while HO Soetta benefits from a more strategic location. However, visual representation of products, company colors, and signage remain insufficient. This study highlights the importance of integrating corporate identity into architectural design to strengthen the company's character and competitive presence.